The influence of individual counseling in improving learning motivation for students - Cindy Marisa (TERAPUTIK: Jurnal Bimbingan dan Konseling, 2017)
This study aimed to find out about the Effect of Individual Counseling in Improving Student Learning Motivation. Quantitative research method used in this research is Nonequivalent Control Group Design, this design is similar to Pretest-Posttest Control Group. The samples in this study were students who amounted to 10 respondents, through purposive sampling technique. The research instrument used in this study is a questionnaire. Data analysis technique is done by calculating the validity test, reliability test, normality test, linearity test and hypothesis test with SPSS version 20.0. This research showed, there was a significant effect of individual counseling in improving student learning motivation, with the result of a coefficient of Sig. (2-tailed) Of 0.000 <0.05 then it was decided that Ho was rejected, and H1 accepted. With R2 value of 0,866, which means, individual counseling give contribution as much 86,6% in improving student learning motivation.